2018
DOI: 10.7150/jca.22329
|View full text |Cite
|
Sign up to set email alerts
|

Targeting hepatocarcinogenesis model in C56BL6 mice with pan-aurora kinase inhibitor Danusertib

Abstract: Background: To elucidate the expression of Aurora kinases (AURK) and the anticancer effects of pan-aurora kinase inhibitor Danusertib in hepatocarcinogenesis model in C56Bl6 mice.Methods: Thirty mice C56Bl6 were randomly divided into Group A or control, Group B animals who underwent experimental hepatocarcinogenesis with diethylnitrosamine (DEN), and Group C animals with DEN-induced hepatocarcinogenenesis that treated with pan-aurora kinase inhibitor Danusertib. Primary antibodies for immunochistochemistry (IH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…HDACi were shown to play a crucial role in cancer progression through regulation of cell proliferation and apoptosis. 33 Although apoptosis has been reported to be a rare event in early HCC lesions in mouse, 29,30 in our study despite the low number of apoptotic cells, morphometric analysis revealed a significant increase of Caspase-3-positive (apoptotic) neoplastic cells in Romidepsin-treated HCC mice, as compared to their non-treated counterparts, which supports a role of Romidepsin in promoting apoptosis. 23 This was further strengthened by the significant elevation of BAD, a major apoptosis regulator, detected in serum of Romidepsin-treated mice, as compared to the HCC untreated controls.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…HDACi were shown to play a crucial role in cancer progression through regulation of cell proliferation and apoptosis. 33 Although apoptosis has been reported to be a rare event in early HCC lesions in mouse, 29,30 in our study despite the low number of apoptotic cells, morphometric analysis revealed a significant increase of Caspase-3-positive (apoptotic) neoplastic cells in Romidepsin-treated HCC mice, as compared to their non-treated counterparts, which supports a role of Romidepsin in promoting apoptosis. 23 This was further strengthened by the significant elevation of BAD, a major apoptosis regulator, detected in serum of Romidepsin-treated mice, as compared to the HCC untreated controls.…”
Section: Discussionsupporting
confidence: 66%
“…For testing the effects of Romidepsin on the Wnt/β-Catenin signaling pathway, which is activated in liver cancer, 47,48 we selectively examined catenin (cadherin associated protein), beta 1 (β-catenin) and the dickkopf WNT signaling pathway inhibitor 1 (DKK1). As we have previously described, 30 with β-catenin-specific IHC, DENinduced hepatocellular adenomas are clearly discernible from adjacent non-tumoral liver tissue due to a denser membrane staining. In the present study, this staining pattern was seen not only in adenomas, but in early small-sized HCC lesions as well.…”
Section: The Inhibition Of Hdac1/2 Affects Pi3k/ Akt But Not Wnt/β-catenin Signaling In Hccsupporting
confidence: 59%
See 2 more Smart Citations